Electronics recycling as an energy efficiency measure – a Life Cycle Assessment (LCA) study on refrigerator recycling in Brazil. (15th August 2016) - Foelster, Anne-Sophie; Andrew, Stefan; Kroeger, Leonardo; Bohr, Philipp; Dettmer, Tina; Boehme, Stefan; Herrmann, Christoph
Abstract: This paper explores the environmental impacts of a refrigerator recycling system in Brazil and quantifies its ecological advantages over primary resource production through a Life Cycle Assessment based on ISO 14040. The Life Cycle Assessment (LCA) accounts for savings of 720 kg CO2 -eq per recycled refrigerator on average, thus demonstrating that an environmentally sound recycling process holds substantial emission reduction potential. In addition, the application of the recycling process in conjunction with collection and reverse logistics of refrigerators in a recycling system can reduce energy demand in Brazil by an average of 1.5 GJ per recycled unit. As a result, refrigerator recycling systems qualify as a valid and scalable energy efficiency measure in accordance with the Brazilian national framework for the evaluation of energy efficiency projects (PROPEE). The energy economics for projects based on recycling systems are shown for the 30 largest energy distributors in Brazil. Available budgets, calculated with diagnostics undertaken in conformity with the International Performance Measurement and Verification Protocol (IPMVP) for a threshold value (cost-benefit ratio = 0.8), clearly indicate the viability and competitiveness of these recycling systems as project opportunities for energy conservation under the national energy regulation agency ANEEL's energy efficiency program (PEE). Highlights: Refrigerator recycling can save up to 9.6 PJ-eq. of primary energy or 1.3 TWh/a. Emissions of 4.7 million tonnes of CO2 -eq. could be avoided. Life Cycle Assessment can evaluate recycling-based energy efficiency projects. Contributes to the Brazilian framework to evaluate energy efficiency projects.